KAMUS TEMATIK SAINS SEBAGAI UPAYA MENINGKATKAN PENGUASAAN KOSA KATA BAHASA ARAB MAHASISWA BIOLOGI - Nurul Hidayah; Umi Kulsum Qomariah (Al-Lahjah, 2020)
Abstract The difficulty of students in mastering Arabic vocabulary is one of the obstacles in learning Arabic. Especially in the vocabulary related to biology which is still very rarely found in other dictionaries. To solve this problem, the researchers compiled an Arabic science dictionary. Another goal that the researcher hopes is to increase the mastery of Arabic vocabulary for students of the faculty of education, especially biology study program. The research methodology used by researchers is using research and development methodology or better known as R&D. The research steps taken by the researcher are as follows: the first stage is defining, the second stage is Design, the third stage is Development, and the last stage is Dissemination or abbreviated as 4D. In the form of data presentation, the researcher used descriptive qualitative data presentation type, namely using the form of data presentation using words instead of numbers. The results obtained by the researchers were the increased mastery of Arabic vocabulary, students could know the proper pronunciation of Arabic vocabulary, the curiosity to know information about biology words was getting higher, and finally the increased motivation to learn Arabic increased. Keywords: Science Thematic Dictionary, Arabic Vocabulary, Biology Students.